Evaluación de los desafíos en la postulación de proyectos a la Convocatoria 2022 del CONACYT: análisis de formatos, guías, sistema de postulación e información (Revista Científica UCOM Scientia, 2025)
This study aims to analyse the formats, guidelines, and relevant information for applications to CONACYT calls, identify the main obstacles researchers face, and propose strategies to improve management and participation in these calls.A mixed-method approach with a descriptive and non-experimental design was adopted. The research included reviewing documentation, such as Frequently Asked Questions (FAQs), analysing open data from projects funded by CONACYT, and applying a questionnaire via Google Forms. In addition, in-depth interviews were conducted with researchers who participated in the 2022 Call.The study revealed several difficulties, mainly related to the complexity of the application guides, strict eligibility criteria, and technical limitations of the Application System to Instruments (SPI). These challenges represent significant barriers for researchers, limiting their ability to participate effectively in the calls.Based on these findings, a series of improvements are proposed aimed at simplifying the application process and facilitating greater researcher participation. Recommendations include revising eligibility requirements, simplifying application guides, and optimizing the SPI to make it more accessible and efficient. These strategies have the potential to improve the management of calls and increase researcher participation and success in future applications.
Keywords: Science and Technology; Call for Proposals; Project Management; Research and Development